Fiskalföderalismus in Europa - Homburg, Stefan, 1961- (Schriften des Vereins für Socialpolitik, Gesellschaft für Wirtschafts- und Sozialwissenschaften, 1997)
Fiscal federalism in Europe. The Financial Sciences Committee ("Finanzwissenschaftlicher Ausschuss") discusses the financial problems affecting the German reunification between 1992 and 1995. In addition, in a general meeting in 1996 in Hamburg it turns its attention on the EU. Three articles discuss the financial selection process and systems - competition between states from an economic point of view, the reasons and consequences of a inter-state compensation system, and the regional dimension of the financial system of the EU